Perempuan Di Titik Nol: Female, Feminine, Dan Feminist - Isnaini, Heri (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2024)
Understanding the concepts of female, feminine, and feminist is often framed in patriarchal power so that the three concepts seem vague and taxa. In feminist literary studies, the position of women, both as biological, culturalist, and political selves, has a very important role in manifesting their self-actualization. R.A. Kartini was allegedly a figure of feminism in Indonesian culture long before the women's movement in America had distinguished these three concepts. Kartini's concept of women is important because it places women precisely in biological, culturalist, and political frameworks. This article will discuss the concept of women in the lens of women biologically (female), culturalist (feminine), and political (feminist) in the context of the novel Perempuan di Point Zero by Nawal El Saadawi. The method used is descriptive qualitative analytic with novel as the source as well as research data. The discussion in this study uses a feminist literary framework that places women as objects of study so that women can be placed as individual, social, and political creatures as a whole and appropriate. The results showed that women were not placed in appropriate positions in this novel by El Saadawi so that more comprehensive emphasis and explanation of the position of women both individually, socially, and politically needed. Thus, women can be manifested as individual, social, and political beings more fully.